How might climate change impact water safety and boil water advisories in Canada? - Sara Moghaddam-Ghadimi; Audrey Tam; Usman T. Khan; Stephanie L. Gora (Canadian Science Publishing, 2023)
A boil water advisory (BWA) informs the public that there is an increased level of risk associated with their water and that they should boil it before consuming. Studies show that small communities in Canada are particularly likely to experience repeat and long-term BWAs. Climate change has led to changes in precipitation and temperature patterns, leading to region-specific impacts such as increased frequency, severity, or variance in floods, forest fires, droughts, freezing rain, and sea water intrusion. Academic and non-academic "grey" literature was reviewed to establish the most likely impacts of climate change on water treatment and infrastructure. Anonymized data from public drinking water systems in Canada was analyzed to determine the most common causes of BWAs between 2005 and 2020. Most BWAs reported were related to breakdowns/malfunctions along the distribution, though inadequate disinfection residual and turbidity or coliforms in the treated water were also common. Furthermore, statistical analysis of the data showed seasonal trends in some of these parameters. The results of this study suggest that increased precipitation, flooding, permafrost degradation, and forest fires are likely to have significant impacts on water safety in Canada. Highlights: Climate change effects are expected to worsen many current water challenges. Climate change will disproportionately impact small, rural, and remote water utilities. Water distribution systems are the main source of water safety risk in Canada. Groundwater-supplied systems experience a disproportionate number of BWAs. Seasonal trends in BWA reasons provide opportunities for targeted mitigation.